Kepercayaan Diri dalam Penyampaian Pendapat pada Mahasiswa Awal Universitas Muhammadiyah Surakarta - Pradana, Irvan Dicky, Rini Lestari, S.Psi, M.Si (2016)
Abstract. The purpose of this research is epressed and know konfidence in communicating opinions in students early Muhammadiyah University Surakarta. Data collection method to research this using interviews. Informants in this research involving 3 men and 2 women with characteristics: student the start of the semester one and two at the University Muhammadiyah Surakarta. The results of the study showed that confidence in communicating opinions in students the first half the beginning were there are 3 informants who believe themselves when asked to pass on the opinion in show with the behavior informants that seeks to be indifferent over his opinion, informants trying to ventured to have an opinion then informants see and ask his friends on the that has been mentioned. And are 2 an informant who is not confident when asked to pass on the opinion in show with behavior informants who less sure of the ability yourself so that informants experienced fear, shame, confused, and really nervous when will pass an opinion in front of common, less free convey the idea the trying to smallest possible to communicxate in forum. An informant who have convidence high informants trying to be demonstrated to be indifferent when giving his opinion in front of common. Nevertheless, informants trying to overcome these things with prepares matter in hand and try to opening up for get input positive from others. For example, informants receive the inputs from his friend when informants have doubts in to the delivery of opinion, in addition informants trying to ventured asked friend who active and was confident it in to the delivery of opinion.